STRATEGIES FOR POPULARIZING THE MEDIA LEAGUE WITHIN THE RUSSIAN SPORTS MEDIA ENVIRONMENT - Zuikina K.L. ,; Mudrik S.V. ,; KhomichD.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify and characterize key practices in promoting the Media Football League (MFL) in Russia. Methods and structure of the study. In the course of working on the study, five semi-structured in-depth interviews were conducted with representatives of the media league management, media football teams, and sports journalists covering MFL competitions. All interviews took place from September to November 2024. The interview guide included three blocks of questions covering the MFL activities from different angles. The interviews were conducted anonymously. Results and conclusions. It was found that the main media tools for promoting the MFL are YouTube and Telegram. In addition, cooperation with traditional sports media is practiced. An important factor in promoting MFL content is its focus on its target audience. Team representatives actively interact with their audience both offline and online, talking about the lives of MFL team players in various media formats and organizing meetings with fans. Thus, individual elements of the media football promotion strategy can be used in developing media strategies for professional football teams.